2019
DOI: 10.1038/s41598-018-35448-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity in remnants of natural mountain forests under conservation-oriented management

Abstract: The structure of forests is an important stabilizing factor regarding ongoing global climate and land use change. Biodiverse mountain forests with natural structure are one of the ecosystems most endangered by these problems. We focused on the mountain forest islands of European beech (Fagus sylvatica) and their role in the natural distribution of organisms. The study area was situated in the oldest Czech national park, Krkonoše (385 km2), which is the highest mountain ridge in the country. We studied multi-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
2
15
0
1
Order By: Relevance
“…In support, Parlade et al [42] have shown that, in P. sylvestris stands, a different intensity of forest management has little effect on the overall diversity of soil fungi. The diversity and composition of fungal communities may also depend on the forest structure, i.e., the age and composition of the tree species [23,26], which together with other factors may determine the habitat heterogeneity [4]. As both managed and unmanaged stands within each national park were in the same geographical area and with similar environmental conditions, it appears that the management abandonment had little effect on the stand structure, which remained largely unchanged and resembled managed forests ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In support, Parlade et al [42] have shown that, in P. sylvestris stands, a different intensity of forest management has little effect on the overall diversity of soil fungi. The diversity and composition of fungal communities may also depend on the forest structure, i.e., the age and composition of the tree species [23,26], which together with other factors may determine the habitat heterogeneity [4]. As both managed and unmanaged stands within each national park were in the same geographical area and with similar environmental conditions, it appears that the management abandonment had little effect on the stand structure, which remained largely unchanged and resembled managed forests ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ca. 10% of the forest area in Europe is left unmanaged [4]. In unmanaged forests, natural disturbances such as wind throws or forest fires lead to heterogeneous structure and different successional stages of forest development [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it is known, the lack of opportunities to expand the amount of land fund is constantly improving the social, economic and ecological significance of the land, as the industry has been growing from year to year [9]. Indeed, it is expedient to take into account market relations, taking into account the importance of society's production, strictly adhering to new economic relations.…”
Section: Graph 3 Land Use Change Altyaryk Districtmentioning
confidence: 99%